2018
DOI: 10.1051/0004-6361/201732436
|View full text |Cite
|
Sign up to set email alerts
|

Major impact from a minor merger

Abstract: Context. Minor mergers are important processes contributing significantly to how galaxies evolve across the age of the Universe. Their impact on the growth of supermassive black holes and star formation is profound – about half of the star formation activity in the local Universe is the result of minor mergers. Aims. The detailed study of dense molecular gas in galaxies provides an important test of the validity of the relation between star formation rate and HCN luminosity on different galactic scales – from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…High-density tracer molecules are expected to reside in the inner core of giant, star-forming molecular clouds and could potentially probe an ISM component that is distinct from that probed in the low-to-mid-J CO, or [C i] lines. Different spatial distributions have been observed in low-redshift (U)LIRGs (see, e.g., Scoville et al 2015Scoville et al , 2017König et al 2018), where dense regions are located within the starburst cores and embedded in diffuse, colder gas reservoirs. High-redshift lensed SMGs could also have such configurations and, in this case, spatially integrated emission line fluxes and profiles could be strongly affected by differential magnification (Hezaveh et al 2012;Serjeant 2012), introducing high uncertainties on the diagnostics from line ratios.…”
Section: Discussion On Differential Lensingmentioning
confidence: 99%
See 2 more Smart Citations
“…High-density tracer molecules are expected to reside in the inner core of giant, star-forming molecular clouds and could potentially probe an ISM component that is distinct from that probed in the low-to-mid-J CO, or [C i] lines. Different spatial distributions have been observed in low-redshift (U)LIRGs (see, e.g., Scoville et al 2015Scoville et al , 2017König et al 2018), where dense regions are located within the starburst cores and embedded in diffuse, colder gas reservoirs. High-redshift lensed SMGs could also have such configurations and, in this case, spatially integrated emission line fluxes and profiles could be strongly affected by differential magnification (Hezaveh et al 2012;Serjeant 2012), introducing high uncertainties on the diagnostics from line ratios.…”
Section: Discussion On Differential Lensingmentioning
confidence: 99%
“…Observational studies of the dense-gas reservoirs in lowredshift star-forming galaxies started about three decades ago (e.g., Nguyen et al 1992), followed by extended surveys of HCN line emission in luminous and ultra-luminous infrared galaxies (ULIRGs) and normal spirals (Gao & Solomon 2004a,b). Since then, HCN and HCO + detections have been extensively used to characterize the dense interstellar medium (ISM) of local (U)LIRGs (e.g., Graciá-Carpio et al 2008;Juneau et al 2009;García-Burillo et al 2012), including diagnostics for the physical conditions of the gas from line excitation modeling (see, e.g., Papadopoulos et al 2014, for NGC 6240 and Arp 193) and spatially-resolved studies with the NOrthern Extended Millimeter Array (NOEMA) and Atacama Large Millimeter/submillimeter Array (ALMA) interferometers (Chen et al 2017;König et al 2018;Imanishi et al 2019). The reliability of each molecule as a proxy of the overall dense-gas content was discussed in Papadopoulos (2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More representative studies have found starburst galaxies that have HCN/HCO + enhancements similar to the enhancements seen in AGN (e.g., Costagliola et al 2011;Privon et al 2015;Martín et al 2015;König et al 2018;Harada et al 2018), where the relative starburst-AGN strength has been primarily assessed using the mid-infrared (MIR) 6.2 µm polycyclic aromatic hydrocarbon (PAH) equivalent width (EQW). This suggests two possibilities: 1) the HCN/HCO + enhancements trace an alternate physical process than AGN activity, or 2) these MIR classified starbursts host AGN that are behind obscuring screens sufficiently thick to render MIR diagnostics ineffective.…”
Section: Dense Molecular Gas Tracers and Active Galactic Nucleimentioning
confidence: 99%
“…NGC 3801 could be at an earlier stage of an NGC 2685like merger (Hota et al 2012). The merging event ∼2-3 Gyr ago is presumably responsible for nuclear-ring in NGC 7742 (Martinsson et al 2018), while the minor merger ∼200 Myr ago (Knierman et al 2012(Knierman et al , 2013 is responsible for the central dust in NGC 2782 and in NGC 4194 (König et al 2018). Balcells (1997) argues that the dusty disk, two tidal tails, and shells in E-type NGC 3656 is the outcome of a disk-disk major merger.…”
Section: Hidden Coherent Featuresmentioning
confidence: 99%